The Effect of Learning Approach and Arm Muscle Power on Tennis Drive Stroke Skills - Hanik Liskustyawati; Sri Santoso Sabarini; Rony Syaifullah; Waluyo; Agus Mukholid; Baskoro Nugroho Putro; Suratmin (Universitas Pendidikan Ganesha, 2025)
The learning approach plays a crucial role in enhancing technical skills in tennis. However, in practice, theoretical approaches are often overlooked, as most sports activities are carried out directly on the court. Therefore, this study aimed to examine the effects of various learning approaches and physical factors on tennis drive stroke skills. Specifically, the study analyzed the impact of the Teaching at the Right Level (TaRL) approach, the influence of arm muscle strength and gender, as well as the interaction among these factors on the improvement of drive stroke performance. An experimental method with a 2×2 factorial design was employed, involving 64 student participants. Drive stroke performance was assessed using the Forehand Groundstroke Tennis Test Accuracy (Jennifer Love Hewitt Test). Data were analyzed using SPSS version 25.0, with normality and homogeneity tests set at α = 0.05. The results indicated that the TaRL learning method yielded Sig. = 0.00 < 0.05, suggesting that this method can enhance technical performance in tennis. Furthermore, arm muscle strength and gender obtained Sig. = 0.667 > 0.05, indicating that physical strength and gender do not play a critical role in drive stroke outcomes. Finally, no interaction was found among learning approach, arm muscle strength, and gender on drive stroke skills, with Sig. = 0.490 > 0.05. These findings highlight the importance of personalized learning strategies over physical attributes in developing skills for the tennis drive stroke.